2022
DOI: 10.1002/ejic.202101056
|View full text |Cite
|
Sign up to set email alerts
|

Soft Metal Cations Trigger Sandwich‐Cluster Luminescence of a New Au(I)‐Vinylimidazolate Cyclic Trinuclear Complex

Abstract: Dedicated to Professor Rinaldo Poli on the occasion of his 65th birthday, with admiration and with many congratulations for all his scientific achievementsThe formation of heterobimetallic complexes from parent cyclic trinuclear complexes (CTCs) of gold(I) has become straightforward in recent years with this team and others showing that the strategy leads to strengthened AuÀ M' bonding and optoelectronic properties. A new gold(I)-vinylimidazolate CTC, 1, was prepared and the formation of highly emissive sandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…2b, 1-I shows a bright emission peaked at 570 nm, whereas the emissions of 1-Cl and 1-Br remain almost unchanged from their room temperature positions (albeit with a significant decrease of the full width at half maximum, FWHM, as expected due to decreased thermal broadening at cryogenic temperatures). 47 The emission lifetime profiles of the three 1 solids are recorded in Fig. 2c and d.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…2b, 1-I shows a bright emission peaked at 570 nm, whereas the emissions of 1-Cl and 1-Br remain almost unchanged from their room temperature positions (albeit with a significant decrease of the full width at half maximum, FWHM, as expected due to decreased thermal broadening at cryogenic temperatures). 47 The emission lifetime profiles of the three 1 solids are recorded in Fig. 2c and d.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…The formation of D/A systems using CTCs, depending on their p-acid or p-basic behaviour, can be achieved by interaction with small organic molecules, 8 with Lewis acids or bases, [15][16][17] by the stacked combination of CTCs with complementary p-acidic/p-basic properties, 4,18 and, finally, by clustering with soft metal cations such as (Cu(I), Ag(I), Tl(I)). 16,18,19 Remarkably, CTCs stack with small aromatic moieties, like benzene, 7 toluene, 7 mesitylene, 10 TCNQ and hexafluorobenzene (TetraCyaNoQuinodimethane), 8 and extended arene systems like naphthalene 6 and nitrofluorene 9 (see Scheme 1) to form isolated binary D/A or extended supramolecular structures of the type {ADAD} n , {ADDA} n (where A = acceptor, D = donor, with n going from 2 to infinite). The formation of extended structures has been extensively observed in the solid state, and the persistence of oligomeric structures of D/A adducts was detected in solution by PGSE determination.…”
Section: Introductionmentioning
confidence: 99%
“…Our model system consists of a Cu­(I) cyclic trinuclear complex (CTC). Such CTCs represent excellent structural platforms for both intra- and intermolecular metal–metal interactions with orthogonal orientations, providing an excellent platform for fundamental understanding of direction-dependent metallophilicity toward optoelectronic device, sensing, and catalysis applications, among others. Our previous studies have identified the critical role of metallophilicity in the phosphorescence of Cu CTCs, , making such systems promising for both fundamental understanding and applications in pressure sensing. However, it remains elusive to identify the distinct roles of inter- and intratrimer metal–metal interactions in their properties.…”
mentioning
confidence: 99%